Are women more likely to engage in extra green behaviors in the workplace? Gender differences in the spillover effect from employee in-role to extra-role green behavior - Wang, Xinnan; Jin, Jiafei; Xu, Jialiang; Khan, Mehedi Hasan (Frontiers in Psychology, 2025)
IntroductionWith the growing importance of green development, organizational research pointed that employee green behavior is an important micro foundation to addressing the environmental challenge. While past studies have categorized the in-role and extra-role green behavior as two dimensions of employee green behavior from the job performance perspective, they have overlooked the potential interaction between the two types of green behavior. This oversight may hamper organizations’ green efforts since deeper engagement in green behavior needs more psychological motivations compared to compliance with green management policies. According to cognitive consistency theory, this study explores employees’ psychology reactions to in-role green behaviors, and how these psychological changes induce extra-role green behaviors.MethodsSurvey data collected in two times from 351 employees from 8 companies in China to assess the proposed hypothesis. SPSS 25 and Smart PLS 3.0 were used to test the theoretical model.ResultsResults show that reflective moral attentiveness and person-organization fit mediate the spillover between in-role to extra-role green behavior. Moreover, these effects were moderated by employee gender: reflective moral attentiveness plays a more important role for women in the green behavior spillover process; conversely, in-role green behaviors lead to stronger person-organization fit for man than for woman.DiscussionThis study provides unique insights into the potential interaction between the two types of green behavior. Furthermore, the psychological mechanisms of this behavioral change are different for male and female employees. Companies should take these differences into account when developing green management policies.